Leveraging Augmented Reality (AR) and Interactive Media to Enhance Elementary Students’ Mastery of Scientific Concepts: A Cross-Regional Study in West Java, Indonesia - Novianti Muspiroh; Asep Kurniawan; Imam Tabroni (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study evaluates the effectiveness of Augmented Reality (AR) and interactive media in improving elementary students’ understanding of abstract science concepts such as the respiratory system, force and motion, and ecosystems in West Java, Indonesia. Novelty: Unlike many studies that focus on technology infrastructure, this research highlights the role of teacher creativity and local relevance, positioning AR as a driver of pedagogical change rather than a mere digital tool. Methods: A mixed-methods design was applied, involving 530 fifth-grade students and their teachers through pre-/post-tests, classroom observations, interviews, and case studies. Results: Quantitative findings showed significant learning gains (average +21.7 percentage points, p < 0.01), with higher AR usage linked to better outcomes. Qualitative data revealed that AR fostered student engagement and reflection, while teachers adopted more facilitative roles. Case studies further indicated that success was shaped by local adaptation and teacher innovation rather than infrastructure alone. Conclusions: The study recommends context-aware AR content, digital pedagogy training, and equitable access policies. AR is affirmed as a transformative paradigm that connects abstract science with meaningful, inclusive, and localized learning experiences.